District heating system analysis within the urban transformation of Kiruna - Vesterlund, Mattias (Luleå tekniska universitet, Energivetenskap, 2014)
The urban transformation that is taking place in Kiruna, a Swedish town well above the Arctic Circle in the sub-arctic climate, is due to the ground deformation caused by iron ore mining and it is affecting all the infrastructures of the town. This thesis focuses on the studies about the district heating for the town of Kiruna. In the field of district heating it is important to have a good knowledge about network behavior, especially if network structure is meshed, in order to understand how the flow is distributed in each pipe within the network. This thesis describes the development of a method for the simulation of district heating networks that makes it possible to analyze and study complex networks with meshed structure, something that has not been possible before. The thermal losses for each pipe type are required as a fundamental input for the simulation. A fictitious pipe series has been created so that its loss matches the losses in the real network. It has been found that the created series is close to the series with the highest losses that is manufactured today. When redesigning the network structure to deal with the urban transformation, an investigation is performed regarding how new low energy building can be heated. This investigation shows that the only heating system that fulfills the guidelines stated by the Swedish authorities about indoor climate is the floor heating. A techno-economical evaluation shows that the cheapest heating technology is an air to air heat pump. In order to make district heating attractive as a heating source for house owners a vigorous price reduction is needed.